Trajectories of internalizing and externalizing symptoms among adults with autism spectrum disorders. (27th November 2015) - Woodman, Ashley C.; Mailick, Marsha R.; Greenberg, Jan S.
Abstract: Individuals with autism spectrum disorder (ASD) experience higher rates of psychopathology than their typically developing peers or peers with other intellectual or developmental disabilities. Little is known about the developmental course of psychiatric symptoms such as internalizing and externalizing behaviors in this population. Individual characteristics and aspects of the family environment may explain variability in outcomes for adults with ASD. The present study extends our current understanding of psychopathology among individuals with ASD by examining group-based trajectories of internalizing and externalizing symptoms in adulthood. Overall, the results showed that symptoms became less severe over time. Distinct patterns of change in psychopathology were observed and associated with differential profiles of psychotropic medication use, comorbid mental health diagnoses, and residential placement. The likelihood of following each developmental trajectory was estimated based on characteristics of the adults with ASD (gender, adaptive behavior, and autistic symptoms) and maternal expressed emotion (criticism and warmth). Maternal criticism and warmth were identified as key risk and protective factors, respectively, with important implications for future research and intervention for individuals with ASD.